Strategies toward anode stabilization in nonaqueous alkali metal–oxygen batteries. Issue 58 (1st July 2022) - Zhou, Congcong; Lu, Kangkang; Zhou, Shiyu; Liu, Yihao; Fang, Weiwei; Hou, Yuyang; Ye, Jilei; Fu, Lijun; Chen, Yuhui; Liu, Lili; Wu, Yuping
Abstract : This highlight demonstrates the challenges and latest progress in stabilizing the metal anode in nonaqueous alkali metal–oxygen batteries. Abstract : Alkali metal–O2 batteries exhibit ultra-high theoretical energy density which is even on par with fossil energy and are expected to become the next generation energy storage devices. However, to maintain the advantages of high energy density of alkali metal–O2 batteries, the reversibility of alkali metal anodes with high capacity is of vital importance. But the alkali metal anode with high chemical activity often faces a variety of challenges, including various side reactions, dendrite formation and volume expansion. In this highlight, we focus on the challenges faced by alkali metal anodes in alkali metal–O2 batteries and introduce the latest strategies to effectively stabilize the metal anode. Future perspectives are pointed out, which are valuable for the further development of nonaqueous alkaline metal–O2 batteries.